ILLICIT ENRICHMENT AND PANCASILA: SYNERGY FOR A JUST CRIMINAL LAW REFORM - Eldi Nasali; Muhammad Mustofa; Lilik Mulyadi (Adisam Publisher, 2025)
Corruption has been proven to weaken democracy, hinder access to justice, and undermine fairness and equality in society. Despite efforts to combat corruption, the global Corruption Perception Index (CPI) remains concerningly low, with Indonesia's CPI score stagnating at 34. A significant challenge in Indonesia's fight against corruption is the lack of criminalization of specific corrupt practices, such as illicit enrichment. Illicit enrichment, defined under Article 20 of the United Nations Convention Against Corruption (UNCAC), involves the significant increase in the assets of a public official that cannot be reasonably explained by lawful income. This research explores the harmonization of Pancasila principles with the formulation of illicit enrichment offenses to strengthen Indonesia's anti-corruption framework. This research utilizes normative legal methods by adopting statutory, conceptual, comparative, approaches. The nature of this research is descriptive-prescriptive. The data that has been collected is analyzed using the content analysis method. The analysis reveals that Indonesia's stagnation in the CPI score reflects deep-rooted systemic issues, including inadequate enforcement of anti- corruption laws and lack of transparency. The absence of specific legal provisions targeting illicit enrichment allows corrupt officials to amass unexplained wealth without facing legal repercussions. Aligning anti-corruption measures with Pancasila principles, such as justice, humanity, unity, democracy, and social justice, is essential. These principles support the need for stringent asset declaration regulations, transparency, and accountability. Criminalizing illicit enrichment would enhance legal frameworks, close loopholes, and promote integrity in public service. By integrating Pancasila values into anti-corruption legislation, Indonesia can create a more just, transparent, and equitable society.